(untitled) (Journal of Hama University, 2024)
The aim of the research is to show the impact of the GDP deflator on the market value of the shares of private commercial banks listed on the Damascus Stock Exchange, during the period from 2011 to 2020, using the simple linear regression method to study the impact between the two variables, depending on the statistical analysis program SPSS25, and the results of this study concluded that there is a statistically significant effect of the GDP deflator as one of the indicators of the general price level in the market value of shares in each of the International Bank for Trade and Finance and Qatar National Bank, and the relationship was positive and this is logical as shares provide protection against the risks of rising the general price level, and therefore the fluctuation of the general price level affects the decisions and attitudes of investors in the financial market, while there was no statistically significant effect of the GDP deflator on the market value of shares in Byblos Bank and Syria Gulf Bank.